First limits on the very-high energy gamma-ray afterglow emission of a fast radio burst: H.E.S.S. observations of FRB 150418 - Abdalla, Hassan; Jankowsky, Felix; Quirrenbach, Andreas; Schwemmer, Stephanie; Wagner, Stefan (Astronomy and astrophysics, 2017)
Astronomy & Astrophysics (A&A) is an international journal which publishes papers on all aspects of astronomy and astrophysics